Influence of Seasonality on the Genetic Diversity of Vibrio parahaemolyticus in New Hampshire Shellfish Waters as Determined by Multilocus Sequence Analysis - Ellis, Crystal N. (American Society for Microbiology, 2012)
Risk of gastric infection with Vibrio parahaemolyticus increases with favorable environmental conditions and population shifts that increase prevalence of infective strains. Genetic analysis of New Hampshire strains revealed a unique population with some isolates similar to outbreak-causing strains and high-level diversity that increased as waters warmed.